EXPERIENCE OF ADVANCED FOREIGN COUNTRIES IN ORGANIZING FOOD SUPPLY IN MILITARY UNITS (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article studied the experience of advanced foreign countries qyshinlaru in the provision of food in stationary and field conditions and cited the effectiveness of the use of the principle of outsourcing or insoring in the feeding of troops.